Realistic Cross-Country Consumption Correlations in a Two-Country, Equilibrium, Business Cycle Model - Michael B. Devereux; Allan W. Gregory; Gregor W. Smith (Queen's University, Department of Economics, 1990)
A well-known feature of one-good, multi-agent, Arrow-Debreu economies with identical additively-separable, homothetic preferences is that the consumptions of all agents are perfectly correlated. Such economies are widely used in interpreting business cycles but seem to be inconsistent with observed cross-country correlations of aggregate consumption. This paper provides an example of a two-country real business cycle model in which preferences are not separable between consumptions and labor supply. The model has a simple closed-form solution, and allows for fluctuations in labor supply in equilibrium. Moreover, it generates correlations between national consumption rates which are close to some of those observed in historical data.
Keywords: 330